Relationship between 4-hydroxy-2-hexenal contents and commercial grade by organoleptic judgement in Japanese dried laver Porphyra spp. (1st December 2016) - Tanaka, Ryusuke; Ishimaru, Mami; Hatate, Hideo; Sugiura, Yoshimasa; Matsushita, Teruo
Highlights: Excellent laver contained higher of free amino acids and 5′-nucleotides. Excellent laver contained higher of lipids and lipophilic pigments. Excellent laver contained lower of 4-hydroxy-2-hexenal and propanal. The 4-hydroxy-2-hexenal content was correlated with propanal in laver. Organoleptic judgement was correlated with chemicals related to color and taste. Abstract: To evaluate the correlation between the commercial grade determined by organoleptic judgment panel and chemical substances in dried laver Porphyra spp., we analyzed the contents of free amino acids, 5′-nucleotides, total lipids, fatty acids, α-tocopherol, lipophilic pigments, and aldehydes in several grades of laver that had been classified by an organoleptic judgment panel. Compared with the lower-grade laver samples, the excellent-grade laver samples contained higher concentrations of free amino acids, 5′-nucleotides, total lipids, α-tocopherol, chlorophyll a, and β-carotene and lower concentrations of aldehydes such as 4-hydroxy-2-hexenal (HHE), propanal, butanal, and 1-hexanal, which are formed during lipid peroxidation of n-3 or n-6 polyunsaturated fatty acids. In addition, the HHE content was strongly correlated with the propanal content in the analyzed laver (r 2 = 0.9123). These results showed that the commercial grade assigned by an organoleptic judgment panel was correlated with chemical substances associated with color, taste, and the prevention of lipid oxidation.